The effectiveness of emergency response plan in specialty chemicals company in Malaysia - Amzirin, Mohammad Iqram (Italian Association of Chemical Engineering - AIDIC, 2014)
Data-based decision making, which is an essential element for continuous improvement, helps individuals and teams to assess the efficiency and effectiveness of on-going processes. This paper describes the emergency drill data-based approach in determining the effectiveness of Emergency Response Plan (ERP) in Specialty Chemicals Company in Malaysia. As most ERP are based on personnel response towards an emergency, the study also examines the human factors that contribute to the degree of effectiveness of an ERP. These include analysing each site's ERP communication, employees' understanding of ERP, employees' confidence in site safety, the involvement of employees in ERP related activities and employee readiness to attend emergencies. Specific improvement actions are then recommended based on the critical deficiencies identified, which include improvement of Emergency Response Team deployment to the scene, making muster and headcount mechanism more efficient and enhancing ERP communication to the employees on-site.